Psychometric Properties of the Obsessive-Compulsive Inventory-Child Version (Oci-Cv) in Chilean Children and Adolescents - Vera-Villarroel, P (Public Library of Science, 2015)
In recent years, there has been a considerable increase in the development of assessment tools for obsessive-compulsive symptomatology in children and adolescents. The Obsessive Compulsive Inventory-Child Version (OCI-CV) is a well-established assessment self-report, with special interest for the assessment of dimensions of Obsessive Compulsive Disorder (OCD). This instrument has shown to be useful for clinical and non-clinical populations in two languages (English and European Spanish). Thus, the aim of this study was to analyze the psychometric properties of the OCI-CV in a Chilean community sample. The sample consisted of 816 children and adolescents with a mean age of 14.54 years (SD = 2.21; range = 10-18 years). Factor structure, internal consistency, test-retest reliability, convergent/divergent validity, and gender/age differences were examined. Confirmatory factor analysis showed a 6-factor structure (Doubting/Checking, Obsessing, Hoarding, Washing, Ordering, and Neutralizing) with one second-order factor. Good estimates of reliability (including internal consistency and test-retest), evidence supporting the validity, and small age and gender differences (higher levels of OCD symptomatology among older participants and women, respectively) are found. The OCI-CV is also an adequate scale for the assessment of obsessions and compulsions in a general population of Chilean children and adolescents. Copyright: © 2015 Martínez-González et al.